1975
DOI: 10.1159/000468165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lithium on Electromyographic Recordings in Man

Abstract: (1) EMG investigations in 17 female manic-depressive patients under longterm treatment with lithium salts showed a reduction of the maximal motor nerve conduction velocity (NCV) and of the duration of isolated potentials (IPs) in six cases. These changes, however, were not clearly due to the influence of lithium only. Psychopathology, additional medication, and other variables may have been also responsible for these findings. (2) NCV and IPs as well as the concentration of electrolytes in serum and RBC were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…In agreement with Girke et al (1975), we have found a slight decrease in m.c.v. and increase of M-response duration during Li treatment.…”
Section: Emg Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with Girke et al (1975), we have found a slight decrease in m.c.v. and increase of M-response duration during Li treatment.…”
Section: Emg Findingssupporting
confidence: 91%
“…So we have combined the measurements of serum Li with measurements of RBC Li concentration. Moreover we have carried out correlative studies by EMG (Girke et al, 1975;Pinelli et al, 1972) or EEG investigations (Zakowska-Dabrowska and Rybakowski, 1973;Johnson et al, 1970;Watanabe et al, 1973;Platman and Fieve, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…The great discrepancy between the high incidence of NCV changes in patients under lithium therapy [3] and the rare occurrence of severe polyneuropathy in lithium intoxication is another evidence to support our sugges tion. However, more clinical observations and/or further animal experiments are needed to prove our hypothe sis.…”
supporting
confidence: 69%
“…We make a hypothesis that some undetermined factors other than a high serum lithium level are essential to trigger the development of overt polyneuropathy in lithium intoxication. In view of the proposal raised by Girke et al [3], i.e. that NCV changes in patients under lithium therapy are not clearly due to the influence of lithium only, we have more con fidence to believe that a high serum lithium level is not the only etiological factor for a severe polyneuropathy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation